2016
DOI: 10.1016/j.ssc.2016.01.021
|View full text |Cite
|
Sign up to set email alerts
|

The induced magnetic and electric fields’ paradox leading to multicaloric effects in multiferroics

Abstract: Vopson first published the multicaloric effect in multiferroics in 2012 [M.M. Vopson, Solid State Communications 152, 2067-2070(2012]. However, a closer examination of the multicaloric effect and its derivation leads to a contradiction, in which the predicted changes in one of the order phase at a constant applied field are due to the excitation by the same field. This apparent paradox has triggered the publication of the "Rebuttal of "The multicaloric effect in multiferroic materials", [arXiv:1602.04238]" by… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
6
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 14 publications
0
6
0
Order By: Relevance
“…This is possible due to particular features of multiferroic materials to accommodate multiple ferroic order states within the multiferroic solid and to display cross coupling properties between the ferroic order states. For a given multiferroic material displaying magnetic and polar order phases and magneto-electric coupling properties, the relations describing the multicaloric effect induced electrically or magnetically are [ 80 , 81 , 82 ]: where T is the temperature, C is specific heat capacity of the system per unit volume C = T ( S / T ), µ 0 , ε 0 are the magnetic permeability and dielectric permittivity of vacuum, χ m and χ e are the magnetic and electric susceptibilities, α E and α H are the electrically and magnetically induced magneto-electric coupling coefficients, M is magnetization and P is the electric polarization of the multiferroic system. A full derivation of the multicaloric effect is given in [ 80 ].…”
Section: Measurement Of Magneto-electric Coupling From Thermal Meamentioning
confidence: 99%
“…This is possible due to particular features of multiferroic materials to accommodate multiple ferroic order states within the multiferroic solid and to display cross coupling properties between the ferroic order states. For a given multiferroic material displaying magnetic and polar order phases and magneto-electric coupling properties, the relations describing the multicaloric effect induced electrically or magnetically are [ 80 , 81 , 82 ]: where T is the temperature, C is specific heat capacity of the system per unit volume C = T ( S / T ), µ 0 , ε 0 are the magnetic permeability and dielectric permittivity of vacuum, χ m and χ e are the magnetic and electric susceptibilities, α E and α H are the electrically and magnetically induced magneto-electric coupling coefficients, M is magnetization and P is the electric polarization of the multiferroic system. A full derivation of the multicaloric effect is given in [ 80 ].…”
Section: Measurement Of Magneto-electric Coupling From Thermal Meamentioning
confidence: 99%
“…[141] In recent times, multicaloric materials that can support more than one type of caloric effect have been investigated. [21,29,59,78,[142][143][144][145] Multicaloric phenomena can be envisioned as the superposition of the primary colors of light as shown schematically in Figure 3. The three primary caloric effects, namely, MC, EC, and mC correspond to the three primary colors of light as blue, green, and red, respectively.…”
Section: Wwwadvmatinterfacesdementioning
confidence: 99%
“…[21,29,78,[142][143][144] Since 2012, several groups have theoretically predicted multicaloric effects in various ferroic materials. [145][146][147][148][149] Models depicting the design and optimization of solid-state coolers based on multicaloric oxides have shown that temperature differences as high as 25 K can be created using multilayered structures. [150] The thermodynamic theoretical framework predicts the expectation of multicaloric phenomena in multiferroic materials in a nonindependent manner.…”
Section: Wwwadvmatinterfacesdementioning
confidence: 99%
“…Some of the most promising applications of multiferroic materials have been detailed in [21], one of them being the application to solidstate caloric effects. This stimulated the concept of multicaloric effect in multiferroics, first proposed theoretically in 2012 [22] and followed by several other studies revolving around the same concept [23][24][25][26][27][28][29][30][31][32]. In [23], the generalized theory of the giant caloric effects was introduced, allowing one to describe all possible caloric and multicaloric effects, including those induced by more exotic means of excitation such as mechanical stress [33,34].…”
mentioning
confidence: 99%